PENGARUH VARIASI KADAR SERAT BAJA TERHADAP WORKABILITY DAN KARAKTERISTIK MEKANIK BETON FC' 30 MPA - Siska Apriwelni; Kirtinanda P; Ayu Sinta Aprilia; Anggarani Budi Ribowo; Kevin Chandra Nurwadji; Fadillah Anisa Pandia (LPPM Universitas Abdurrab, 2026)
This study analyzes the effect of steel fiber addition on the workability, compressive strength, and split tensile strength of f’c 30 MPa concrete. Steel fiber contents of 0%, 5%, and 7% by total weight of concrete mix materials (equivalent to 0, ±112.4, and ±157.4 kg/m³, respectively) were investigated. Thirty-six cylindrical specimens (Ø15 cm × 30 cm) were tested at 7 and 28 days per SNI 7656:2012. Steel fiber addition significantly reduced slump values (7.5, 5.0, and 3.0 cm), decreased 28-day compressive strength from 31.97 MPa to 26.79 MPa (5%) and 23.39 MPa (7%), and increased split tensile strength from 2.45 MPa to 4.29 MPa (5%) and 4.20 MPa (7%). One-way ANOVA confirmed significant differences among variations (compressive strength: F = 34.86 > Fₜₐₕₑ = 5.14, α = 0.05; split tensile strength: F = 12.97 > Fₜₐₕₑ = 5.14, α = 0.05). The 5% steel fiber variation proved most effective, delivering the highest tensile strength improvement while maintaining acceptable workability.